Safe and Effective Delivery of Antitumor Drug Using Mesenchymal Stem Cells Impregnated with Submicron Carriers; ACS Applied Materials and Interfaces; Vol. 11 (14) - Timin A. S. Aleksandr Sergeevich; Peltek A. O. Aleksey Olekseevich; Zyuzin M. V. Mikhail; Muslimov A. R. Albert Radikovich; Karpov T. E. Timofey Evgenjevich; Epifanovskaya O. S. (2019, 2019)
Title screen